The biodiversity and epidemiology of potato virus Y (PVY) in Scotland - Davie, Kim (2014)
Potato virus Y (PVY) is considered to be the most serious viral pathogen that affects potato crops worldwide and can cause substantial yield losses. PVY exists as a complex of strains that can be distinguished on the basis of their biology, serology and genome analysis. In recent decades novel recombinant PVYN strains have emerged that can cause Potato Tuber Necrotic Ringspot Disease (PTNRD). It is therefore important to understand the potential threat to the Scottish seed potato industry. This molecular nature of PVY isolates in Scotland was established through the use of partial sequencing, revealing a predominance of isolates belonging to the molecular EU-NTN clade (ca 75%). Assessing the biological characteristics of selected isolates indicated that most isolates in Scotland belong to the biological PVYN type, however PVYE is also present. Molecular analysis of a PVYE isolate has shown that identifying the molecular determinants for vein necrosis production in tobacco is complex. Although it has not been reported from the field in Scotland, PTNRD initiation is possible with most PVYN isolates under optimal climatic conditions. Field trials suggest that PVYEU-NTN is more efficiently transmitted by aphids across a growing season than PVYNA-NTN and PVYO, with a higher than expected proportion of tubers infected with the PVYEU-NTN isolate. This suggests that once plants are inoculated with the virus, PVYEU-NTN isolates are more likely to infect progeny tubers. Taken together, the outcomes of this project should provide a better understanding as of PVY molecular nature in Scotland its pathogenicity and epidemiology with the view to understanding why PVYN variants have become an important threat for the seed potato industry both in Scotland and worldwide.